Evaluation of the current state of the nitrogen in the arrangement aliso kikuyo - Muñoz H, Elizabeth; Pupiales A, Silvia; Navia E., Jorge (Revista de Ciencias Agrícolas, 2011)
The study was realized in the Experimental Center FEDEPAPA, municipality of Pasto, Department of Nariño located to north latitude and 77°18" longitude west, to 2710 msnm, with precipitation average of 840 mm and and a temperature of 13°C, zone of life bs-MB. Evaluates the current state of the nitrate and ammonium in the system aliso (Alnus jorullensis) and grass (Pennisetum clandestinum) in two depths and five distances it was compared with the monoculture of grass and decided the forage production and soil humidity. It presented major levels of nitrate and ammonium in the arrangement aliso+grass that in the monoculture of grass and in the first caps there were major contents of these two elements during the accomplishment of this study, equally it presented major quantities of nitrate that of ammonium. The treatments applied to the arrangement aliso+grass to the humidity of the soil, indicated that the humidity was homogeneous between distances and depths. In the monoculture was observed that this was superior to major depths. For the production of forage they presented significant differences, indicating that the distance affect the production of forage.